The Formulation of Effervescent Granules with Oxalis dehradunensis Raizada Ethanol Extract as an Antioxidant - Mahyuni, Eka Lestari; Harahap, Urip (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2024)
Antioxidants and their health implications are widely studied related to their benefits in reducing free radical exposure. Oxalis dehradunensisRaizada is a type of wild mountain clover containing flavonoids and polyphenols. These contents allow the leaves to be consumed in a more practical, effective, and efficient way by processing the extract into effervescent granules. This experimental study used samples of Oxalis dehradunensisRaizadaethanol extract formulated in the form of effervescent granules. The content included citric acid, tartrate acid, lactose and sodium bicarbonate. The antioxidant activity assays were conducted by DPPH methods including testing the total phenol and flavonoid contents for the extracts and forms of effervescent granules. The total phenol content analysis used the Folin-Ciocalteu method while the total flavonoid content used the colorimetry method. The results identified the extract as the hygroscopic extract which had increasing IC50 for upgraded content of the formula but looked wet and was not stable. The experiment for the formula of effervescent granules was fulfilled by adding povidone, aspartame and polyethylene glycol. It required angle of repose which was 200-400 with a flow time not exceeding 10 seconds. The tap density also fulfilled the requirements, with the smaller the granule tap density, the greater the compression volume. The extract has a good antioxidant with IC50 value which reached near moderate to high levels. Although the formula 4 of effervescent granules was the best, it did not have the best antioxidant activity. Based on the results from the antioxidant activity assays, the extract has good antioxidant activity but it decreased when made into effervescent granules.